Phylloplane associated plant bacteria of commercially superior wheat varieties exhibit superior plant growth promoting abilities. Issue 4 (1st October 2016) - Batool, Fatima; Rehman, Yasir; Hasnain, Shahida
ABSTRACT: Phylloplane of a plant constitutes an important habitat for a variety of microbes many of which play important roles in plant growth. The objective of this study was to compare plant growth promoting (PGP) phylloplane bacteria of three commercially popular wheat varieties, namely Sehar, Faisalabad and Lasani, in order to assess whether better wheat variety harbours better PGP bacteria that play part in its superior yield. Phylloplane bacteria were isolated from the three wheat varieties thrice during the plant growth. The bacterial load increased with the growing season and Sehar variety carried maximum bacterial load (CFUg −1 1.1 × 10 9 ). Succession of bacterial community was also observed during the plant growth. Isolates belonging to Sehar phylloplane produced auxin in highest amounts (52.95 µg ml −1 ) during second sampling when plant was showing rapid growth. Many isolates from all three varieties fixed nitrogen, solubilized phosphates and some isolates also produced hydrogen cyanide. The results clearly indicated that the beneficial bacteria associated with phylloplane of better yielding variety were showing better PGP abilities when compared to their counterparts on low yielding varieties. Isolates exhibiting best PGP profiles were identified as Bacillus, Microbacterium, Acinetobacter, Proteus, Psychrobacter, Pseudomonas, Streptomyces and Kineococcus species through 16S rRNA gene sequencing.